THE MAIN RISKS OF INTERNATIONAL COMMERCIAL BANKS IN FINANCING INFRASTRUCTURE PROJECTS - Саидова Наргиза Шовхи кизи; Тураева Сурия Тельмановна (European Science Publishing, 2026)
Financing infrastructure projects is one of the key areas of activity for international commercial banks, especially in the context of the growing need of developing and transition economies to modernize their transport, energy and logistics infrastructure. At the same time, infrastructure projects are characterized by high capital intensity, long implementation periods, and a significant degree of uncertainty, which creates a wide range of risks for lending banks. The purpose of this article is to provide a comprehensive analysis of the main risks faced by international commercial banks when financing infrastructure projects. This article examines credit, operational, regulatory, political, currency, and legal risks, as well as the specifics of their assessment and management in project finance. Particular attention is paid to the role of the institutional environment and public-private partnerships in redistributing and mitigating banking risks. Based on an analysis of international experience, conclusions are drawn regarding the key factors influencing international banks' participation in infrastructure financing.
Keywords: International commercial banks, infrastructure projects, project financing, banking risks, investments, PPP.